Auditory Spatial Perception without Vision - Voss, Patrice (Frontiers in Psychology, 2016)
Valuable insights into the role played by visual experience in shaping spatial representations can be gained by studying the effects of visual deprivation on the remaining sensory modalities. For instance, it has long been debated how spatial hearing evolves in the absence of visual input. While several anecdotal accounts tend to associate complete blindness with exceptional hearing abilities, experimental evidence supporting such claims is, however, matched by nearly equal amounts of evidence documenting spatial hearing deficits. The purpose of this review is to summarize the key findings which support either enhancements or deficits in spatial hearing observed following visual loss and to provide a conceptual framework that isolates the specific conditions under which they occur. Available evidence will be examined in terms of various spatial dimensions (horizontal, vertical and depth perception) and in terms of frames of reference (egocentric and allocentric). Evidence suggests that while early blind individuals show superior spatial hearing in the horizontal plane, they also show significant deficits in the vertical plane. Potential explanations underlying these contrasting findings will be discussed. Early blind individuals also show spatial hearing impairments when performing tasks that require the use of an allocentric frame of reference. Results obtained with late-onset blind individuals suggest that early visual experience plays a key role in the development of both the spatial hearing enhancements and deficits observed in the early blind.